The analysis of the content of biology books for the fourth grade of science branch in the light of the dimensions of the blue economy - Firas ayal mater, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The high rate of poverty and unemployment, the increase in environmental pollution in many countries of the world, especially developing countries, and the slow global economic growth have prompted researchers to conduct research and studies on how to overcome the obstacles facing the world and invest all efforts and human and material energies to find solutions to the problems of our time and to harness the possibilities offered by the oceans, seas and daylights at the national level to contribute to diversifying investment opportunities and providing job opportunities related to the economic dimension, as well as finding real and realistic solutions to the bad practices that the seas and oceans are exposed to, especially pollution and overfishing related to the environmental dimension and the need to move towards the blue economy and pay attention to it because of its economic importance that depends on the seas And the oceans and their coasts, including fishing, maritime transport, ports, marine mining, marine energy, extractive activities on the seabed, bioprospecting and others.